Gamification on English Reading skills development among superior basic education students at a public institution of Loja city. School year 2022-2023. Gamificación en el desarrollo de habilidades de Lectura en inglés en estudiantes de educación básica superior de una institución pública de la ciudad de Loja. Año lectivo 2022-2023. - Salazar Chamba, Erika Michelle (2023)
The objective of this study was to improve reading skills through the use of the "gamification" technique with students in upper middle school, specifically with a sample of 22 students in the ninth grade of a public school in the city of Loja during the 2022-2023 academic period. Reading is considered a receptive skill because students can acquire and interpret information from written texts through it. In addition, the method used during this research was mixed, with which it was possible to obtain quantitative data (students' grades) using a pretest and a posttest, qualitative data (students' perceptions) were also obtained through a questionnaire and these were corroborated with the use of a checklist. The data analyzed showed a significant improvement in the students' reading levels after applying the "gamification" technique. It was concluded that gamification had an important impact on the students as it improved their behavior, lack of attention, and boredom in the classroom and motivated them to study in a fun but meaningful way. Finally, this study helped novice teachers improve their teaching methods and provided them with new knowledge that can be applied in their professional lives. Key Words: gamification, reading skills, mixed research, reading level, perceptions.